The influence of brand value dimensions on consumer loyalty among young adults: Evidence from Sri Lanka's high-tech market - Fernando Kurukulasuriya Weerasinghe Tharindu Madushanka; Das Ghansham (Marketing (Beograd. 1991))
Consumer loyalty in high-tech markets is challenged by rapid technological change and shifting consumer expectations. Although Consumer Perceived Value (CPV) research exists across various industries, studies on high-tech brand value perceptions in emerging economies, such as Sri Lanka, are limited. This paper examines the influence of brand value dimensions on consumer loyalty in Sri Lanka and provides practical insights. Primary data from 463 university students, collected via a Web-based survey, were analyzed using Statistical Package for the Social Sciences (SPSS) and Analysis of Moment Structures (AMOS). Structural Equation Modeling (SEM) was used to test the hypothesized relationships between macro-level brand associations, perceived value dimensions, and consumer loyalty outcomes. The results of the exploratory and confirmatory factor analyses confirmed the validity of the model, with 16 out of 18 hypotheses supported, demonstrating strong model fit and significant relationships. Macro-level brand associations had a varied but significant influence on brand value dimensions. Functional, social, and emotional values accounted for the most variance in loyalty constructs, while economic and epistemic values showed weaker effects. The findings of this research reinforce and refine the body of knowledge on the CPV concept in high-tech industries.